Liturgical Education of Children in Catholic Church - Silpanus Silpanus (Gaudium Vestrum - Jurnal Kateketik Pastoral, 2020)
The Church should give special attention to children, especially those who were baptized as infants. It would be good for the Church to take advantage of the time that children are being prepared for First Communion and Confession to give them appropriate liturgical education. Moreover, children who have received their First Communion should not yet be left on their own but continue to be accorded diligent pastoral care by the local Church because at this stage and in many cases children thrive in an atmosphere that is less favorable for spiritual progress. Liturgical education and formation intended for children can be very challenging especially during these present times that parents are oftentimes not capable of providing a sustained liturgical experience and exposure to their children. Parents usually relegate to the parish and to the Catholic schools whatever amount and kind of liturgical education can possibly be given to today’s children.